Prediction of premature ventricular complex origin in left vs. right ventricular outflow tract: a novel anatomical imaging approach. Issue 1 (16th July 2018) - Korshunov, Viatcheslav; Penela, Diego; Linhart, Markus; Acosta, Juan; Martinez, Mikel; Soto-Iglesias, David; Fernández-Armenta, Juan; Vassanelli, Francesca; Cabrera, Mario; Borràs, Roger; Jáuregui, Beatriz; Ortiz-Pérez, Jose T; et al.
Abstract: Aims: Left ventricular (LV) outflow tract ventricular arrhythmias (OTVA) are associated with hypertension (HT), older age, and LV dysfunction, suggesting that LV overload plays a role in the aetiopathogenesis. We hypothesized that anatomical modifications of the LV outflow tract (LVOT) could predict left vs. right OTVA site of origin (SOO). Methods and results: Fifty-six (32 men, 53 ± 18 years old) consecutive patients referred for OTVA ablation were included. Cardiac multidetector computed tomography was performed before ablation and then imported to the CARTO system to aid the mapping and ablation procedure. Anatomical characteristics of the aortic root as well as aortopulmonary valvular planar angulation (APVPA) were analysed. The LV was the OTVA SOO (LVOT-VA) in 32 (57%) patients. These patients were more frequently male (78% vs. 22%, P  = 0.001), older (57 ± 18 vs. 47 ± 18 years, P  = 0.055), and more likely to have HT (59% vs. 21%, P  = 0.004), compared to right OTVA patients. Aortopulmonary valvular planar angulation was higher in LVOT-VA patients (68 ± 5° vs. 55 ± 6°, respectively; P  < 0.001). Absolute size of all aortic root diameters was associated with LVOT origin. However, after indexing by body surface area, only sinotubular junction diameter maintained a significant association ( P  = 0.049). Multivariable analysis showed that APVPA was an independent predictor of LVOT origin. Aortopulmonary valvular planar angulation ≥62° reached 94% sensitivity and 83% specificity (area under the curve 0.95) for predicting LVOT origin. Conclusions: The measurement of APVPA as a marker of chronic LV overload is useful for the prediction of left vs. right ventricular OTVA origin.